MODEL FOR METAL REMOVAL IN ELECTROLYTE-PLAZMA TREATMENT OF CYLINDRICAL SURFACES - Yu. G. Alekseev; A. Yu. Korolyov; A. E. Parshuta; V. S. Niss (Наука и техника)
The paper describes development of calculation and experiment model for metal removal in electrolyte-plasma treatment of rotational surfaces. The model for metal removal based on equality of pressures acting on the straight and curved sections of the vapor-gas blanket has been suggested and experimentally substantiated in the paper. The executed investigations have made it possible to determine dependences describing relationship between the intensity of dimensional electrolyte-plasma treatment of rotational parts and technological parameters of process. An expression for calculation of metal removal rate has been determined in the paper.Results of the work have been used for calculation of metal removal while developing technology of multi-stage cylindrical ultrasonic waveguides for blood clots destruction.